Ecological controls on post‐fire vegetation assembly at multiple spatial scales in eastern North American boreal forests. (28th November 2014) - Boiffin, Juliette; Aubin, Isabelle; Munson, Alison D.; Roxburgh, Stephen
Abstract Question In fire‐prone boreal forests, to what extent does fire severity influence understorey plant community assembly? What are the abiotic and biotic factors controlling understorey community regeneration at regional, landscape and local scales? Location Black spruce‐dominated boreal forest in eastern Canada. Methods A taxonomic and a trait‐based approach were combined to evaluate the relative influence of habitat characteristics, burn severity and biotic processes on understorey regeneration at multiple spatial scales. Sampling of understorey vegetation cover was carried out in 133 recently burned plots located in 14 different fires across a 600‐km transect. The spatial hierarchy for sampling consisted of five fire regime zones (regional scale), two to four fires within each zone (landscape) and two to four toposequences within each fire (local). The environmental control of fire severity and habitat characteristics on understorey regeneration was assessed using a canonical redundancy analysis (RDA) and variation partitioning. We investigated environmental and biotic filters of species traits at different scales by modelling trait–spatial assemblages with Moran eigen vector maps (MEMs). Results In spite of the large variability of environmental conditions covered by our sampling design, low depths of burn were measured in the large majority of the studied sites. Incomplete consumption of the forest floor is frequently observed in eastern boreal forests characterized by long fire cycles. In situ biological legacies persisted through the low‐severity fires, which conserved the pre‐fire relationships between plant communities and their environment. As a result, fire severity was neither the unique nor the dominant control on post‐fire regeneration. Habitat characteristics explained a three times higher proportion of variation in species composition. Biotic controls on trait assemblage increased at the two finer scales. Conclusions Severity alone cannot predict understorey vegetation assembly at different scales in the low‐severity fire regime characteristic of the eastern North American boreal forest.